Coronary Artery Disease: Calcium Score of Zero: Not a Gatekeeper to Rule Out Coronary Artery Disease - Truong, Quynh A. (2010)
The Absence of Coronary Calcification Does Not Exclude Obstructive Coronary Artery Disease or the Need for Revascularization in Patients Referred for Conventional Coronary Angiography